Coaggregation of Prevotella intermedia with oral Actinomyces species. - Nesbitt, W E (1993)
Five strains of Prevotella intermedia were examined for their ability to coaggregate with various gram-positive and gram-negative species of oral bacteria. Two of the P. intermedia strains coaggregated with selected Actinomyces species, P. intermedia 27 with Actinomyces viscosus T14V and Actinomyces naeslundii ATCC 12104, PK606, PK984, and PK947, and P. intermedia 113 with Actinomyces odontolyticus WVU 1546 and Actinomyces israelii WVU 838. Exposure of both Prevotella strains but not the Actinomyces strains to heat, trypsin, or proteinase K abolished most coaggregations. All pairs were disaggregated by the addition of sodium dodecyl sulfate, but only those coaggregations involving P. intermedia 113 were reversed by the addition of 2.0 M urea. P. intermedia 27 was sensitive to periodate oxidation, whereas the partner strains were stable to this treatment. Most coaggregations occurred in the presence of saliva; however, reactions involving P. intermedia 27 were not as strong as those of buffer-suspended cells. Treatment of both P. intermedia 113 coaggregations pairs with proteinase K and the results obtained from suspensions of these pairs in saliva suggest that different surface molecules of this P. intermedia strain may mediate each of these coaggregations. These data suggest that all of these coaggregations involve either a protein or glycoprotein on the Prevotella strain, which may interact with carbohydrates or carbohydrate-containing molecules on the surface of the Actinomyces strain.